Relationship between parenting attitudes and children's pre-school education attainment level - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2007)
Parenting attitudes is one of the important factors in child education. This study examined the relation between parenting attitudes of children who have just started primary education and pre-school education attainment levels. 183 parents participated to the study. In order to determine parenting styles, PARI was introduced to the parents. Kruskall Wallis, t-test, One-way Anova and Mann Whitney U tests were utilized to analyze the data. The results revealed that the parents whose children did not attain pre-school education are more productive and more authoritarian. Also, the data showed that there is a negative correlation between the types of parenting attitudes and pre-school education attainment level. However, it was found out that there is no significant relation between democratic parenting attitudes and children's pre-school education attainment levels. It was revealed that the parents of children, who had longer pre-school education attainment, had the highest level of parenting attitude scores. Finally, it was found that parenting attitudes did not change according to the sex of the children.
Keywords: pre-school education; parenting attitudes; primary education